A New Computer Program for Generating Three-Dimensional Plots of Electronic Densities and Related Contour Levels - Nadia Thalmann; Jacques Weber (CHIMIA)
A new three-dimensional plotting program written in FORTRAN is described, which allows an easy visualization of computed electronic densities as well as the corresponding contour levels. Particular emphasis has been placed on (i) the development of new graphical algorithms which allow a smooth plot even for sharp function peaks and (ii) the simplicity of program operation which makes it very easy to use. As an example, the it molecular orbital of ethylene is represented.